The art of instruction : vintage educational charts from the 19th and 20th centuries - Van der Schueren, Katrien; Chronicle Books (Firm) (San Francisco, CA : Chronicle Books, 2011)
Large-scale wall charts were fundamental tools of classroom instruction throughout Europe in the mid-nineteenth and twentieth centuries. Collected here for the first time in one deluxe volume are over 100 of these vintage educational posters now important relics in the history of science, art, and design. From the anatomy of a tulip or an apple tree to that of a hedgehog or starfish, the botanical and zoological images in this collection are captivating with their curious visuals and intricate details. With a compelling introduction about the history of educational charts and their production, The Art of Instruction provides a glimpse into a rich, significant heritage and will enlighten those with an interest in art, design, science, or natural history.
Introduction -- Botany -- Zoology -- Appendix -- Credits -- Bibliography -- References -- Author biography -- Acknowledgments.
Includes bibliographical references.
Keywords: Science -- Charts, diagrams, etc; Posters in education -- History